Surrogacy and women's right to health in India: Issues and perspective - Anu; Pawan Kumar; Deep Inder; Nandini Sharma (Wolters Kluwer Medknow Publications, 2013)
The human body is a wonderful machine. The future of child birth in the form of test tube babies, surrogate motherhood through new reproductive and cloning technology will introduce undreamt of possibilities in the sexual arena. Surrogacy is a method of assisted reproduction whereby a woman agrees to become pregnant for the purpose of gestating and giving birth to a child for others to raise. In some jurisdictions the possibility of surrogacy has been allowed and the intended parents may be recognized as the legal parents from birth. Commercial surrogacy, or "Womb for rent", is a growing business in India. In our rapidly globalizing world, the growth of reproductive tourism is a fairly recent phenomenon. Surrogacy business is exploiting poor women in country like India already having with an alarmingly high maternal death rate. This paper talks about paternity issues and women's right to health in context of surrogacy. Government must seriously consider enacting a law to regulate surrogacy in India in order to protect and guide couples going in for such an option. Without a foolproof legal framework, patients will invariably be misled and the surrogates exploited.